The Teachers’ Manners in Language Use and Classroom Management Interaction in Senior High School - Thoyib, Mastur (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2024)
The purpose of this paper is to investigate the teachers’ manners in language use and classroom management interaction in senior high school. A descriptive research design was adopted in this study. The purpose of this study is to address the research questions, "How are the teachers’ manner in language use in the classroom, and how are the management interactions in the second language classroom?" This study included two instructors from a private SMK in Bogor District as participants. The data collection instrument consists of three questions that teachers must answer. The results demonstrate that home language is an important aspect of language use in the classroom. Furthermore, teachers feel that using role play and creating pair workgroups is vital for teacher-student engagement in the classroom. As a result, it can assist teachers in teaching English as a foreign language in the classroom to become much more successful and communicative. In addition, teachers should behave well in the classroom by smiling, being positive, and being relaxed. The students will benefit from this by having a good day and feeling comfortable while studying English. Additionally, teachers should dress professionally in the classroom to uphold their dignity and the pupils' respect.